Artificial intelligence and the problem of redundant people - A. M. Zuiev, (Ukrainian Cultural Studies, 2020)
Last five-ten years was very productive in development of machine learning creating some kind of artificial intelligence in the foreseen future starts looking realistic. And creating and development of artificial intelligence will raise a lot of ethical questions as well.